INNOVATIVE DEVELOPMENT OF MEDICINE IN THE RUSSIAN FEDERATION - M. Tomova (Вестник университета)
The relevance of the research topics defined by the fact that in the result, introduced in March 2014 in respect of certain business entities of the Russian Federation of sanctions by Western countries, the response of the Government was the development and implementation of the policy of import substitution, which until now have not had the desired success. Low effectiveness of the pursued policy of import substitution is defined, first of all, by lack of a target expenditure of the funds allocated for development of various industries including medicine.